Sulforaphane Ameliorates Bladder Dysfunction through Activation of the Nrf2-ARE Pathway in a Rat Model of Partial Bladder Outlet Obstruction. (28th June 2016) - Liu, Chong; Xu, Huan; Fu, Shi; Chen, Yanbo; Chen, Qi; Cai, Zhikang; Zhou, Juan; Wang, Zhong
Abstract : Purpose . We evaluated the effect of sulforaphane (SFN) treatment on the function and changes of expression of Nrf2-ARE pathway in the bladder of rats with bladder outlet obstruction (BOO). Materials and Methods . A total of 18 male Sprague-Dawley rats at age of 8 weeks were divided into 3 groups (6 of each): the sham operated group, the BOO group, and the BOO+SFN group. We examined histological alterations and the changes of oxidative stress markers and the protein expression of the Nrf2-ARE pathway. Results . We found that SFN treatment could prolong micturition interval and increase bladder capacity and bladder compliance. However, the peak voiding pressure was lower than BOO group. SFN treatment can ameliorate the increase of collagen fibers induced by obstruction. SFN treatment also increased the activity of SOD, GSH-Px, and CAT compared to the other groups. The level of bladder cell apoptosis was decreased in BOO rats with SFN treatment. Moreover, SFN could reduce the ratio of Bax/Bcl-2 expression. Furthermore, SFN could activate the Nrf2 expression with elevation of its target antioxidant proteins. Conclusions . The sulforaphane-mediated decrease of oxidative stress and activation of the Nrf2-ARE pathway may ameliorate bladder dysfunction caused by bladder outlet obstruction.